Associação entre Diabetes Mellitus Gestacional e práticas obstétricas, por características sociodemográficas, em maternidades de Belo Horizonte, Minas Gerais - Vivian Andrezza Alves Andrade (2022)
Introduction: Childbirth care has undergone transformations over the years and the incorporation of various technologies into obstetric practice has contributed to the fact that women are no longer the protagonists of the parturition process, in many circumstances. Population data show that less than 5% of Brazilian pregnant women have experienced childbirth without interventions and that there is a low prevalence of recommended obstetric practices during labor care and a high prevalence of nonrecommended obstetric practices. In this context, there are studies that relate the presence of comorbidities, such as gestational diabetes mellitus (GDM), to a high number of obstetric practices. Thus, studying the association between GDM and obstetric practices in different age groups and sociodemographic contexts becomes important, since, to our knowledge, there are few studies on GDM in Brazil and studies on obstetric interventions are limited, evaluating few interventions or they do not associate chronic diseases, especially GDM. Objective: To estimate the association between GDM diagnosis and obstetric practices, based on the sociodemographic characteristics of pregnant women, in maternity hospitals in Belo Horizonte, Minas Gerais. Methods: This is a cross-sectional study, based on data from the survey “Nascer em Belo Horizonte: Inquérito sobre parto e Nascimento”, involving 1,088 women. Two types of analysis were performed: PCA (Principal Component Analysis) and Cluster. To assess the coexistence between the presence of GDM, health insurance and maternal age over 35 years (exposure) and the presence of obstetric interventions (outcomes), a tertile score of the pattern found was created and the chi square test was used. For the segregation of correlated groups, cluster analysis was used to generate groups that gathered information on the presence or absence of GDM at different age averages. The difference in averages ages between the groups was evaluated using the t test. The associations between the diagnosis of GDM (exposure) and each obstetric practice (outcomes) were based on Pearson's chi-square or Fisher's exact tests, by maternal age clusters, considering a significance of 5%. Results: PCA analysis showed that the pattern was composed of the variables possession of health insurance, advanced maternal age, education, economic class and presence of GDM with the following obstetric practices during labor: lying position, enema, absence of ambulation, use of intravenous access, no diet and cesarean delivery. Higher proportions of these practices were also found in the third tertile of the pattern obtained by the analysis of principal components (p<0.05). The results showed statistically significant associations in the cluster of younger women with GDM in: greater proportion of analgesia during childbirth (50%) compared to non-diabetic women from the same cluster (26.13%) and use of forceps or vacuum extractor (23 .08%) compared to non-diabetic patients (4.85%). In the cluster of older women, who had GDM, there was a statistically significant association for offering some diet (16.67%) when compared to non-diabetic women from the same cluster (13.61%) and greater use of antibiotics during labor (24 .14%) compared to non-diabetic women in the same cluster (9.05%). In the cluster of younger women, it was observed that, when compared to non-diabetic women: they walked more during labor (93.33%), made more use of CTG (cardiotocography) (12.50%), breastfed less in the first hour of the baby´s life (40.00%), had less skin-to-skin contact with the baby (52.00%), made greater use of non-pharmacological methods for pain relief (96.00%), used more intravaginal medication for labor induction (37.50%) and had more episodes of urinary tract infection (68.00%). Conclusion: : It was demonstrated that the presence of the diagnosis of GDM can be a potential risk factor for the use of non-recommended obstetric practices, and this relationship is also enhanced when considering high age, as well as having a health insurance plan.